The effect of starch-based biomaterials on leukocyte adhesion and activation in vitro - Marques, A. P. (2005)
Leukocyte adhesion to biomaterials has long been recognised as a key element to determine their inflammatory potential. Results regarding leukocyte adhesion and activation are contradictory in some aspects of the material’s effect in determining these events. It is clear that together with the wettability or hydrophilicity/hydrophobicity, the roughness of a substrate has a major effect on leukocyte adhesion. Both the chemical and physical properties of a material influence the adsorbed proteins layer which in turn determines the adhesion of cells. In this work polymorphonuclear (PMN) cells and a mixed population of monocytes/macrophages and lymphocytes (mononuclear cells) were cultured separately with a range of starch-based materials and composites with hydroxyapatite (HA). A combination of both reflected light microscopy and scanning electron microscopy (SEM) was used in order to study the leukocyte morphology. The quantification of the enzyme lactate dehydrogenase (LDH) was used to determine the number of viable cells adhered to the polymers. Cell adhesion and activation was characterised by immunocytochemistry based on the expression of several adhesion molecules, crucial in the progress of an inflammatory response. This work supports previous in vitro studies with PMN and monocytes/macrophages, which demonstrated that there are several properties of the materials that can influence and determine their biological response. From our study, monocytes/macrophages and lymphocytes adhere in similar amounts to more hydrophobic (SPCL) and to moderately hydrophilic (SEVA-C) surfaces and do not preferentially adhere to rougher substrates (SCA). Contrarily, more hydrophilic surfaces (SCA) induced higher PMN adhesion and lower activation. In addition, the hydroxyapatite reinforcement induces changes in cell behaviour for some materials but not for others. The observed response to starch-based biodegradable polymers was not significantly different from the control materials. Thus, the results reported herein indicate the low potential of the starch-based biodegradable polymers to induce inflammation especially the HA reinforced composite materials.